2019
DOI: 10.1177/0363546519881445
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transphyseal and Lateral Extra-articular Pediatric Anterior Cruciate Ligament Reconstruction: A Novel Technique to Reduce ACL Reinjury While Allowing for Growth

Abstract: Background: Treatment of anterior cruciate ligament (ACL) injuries in the adolescent population continues to be complicated by an unacceptably high rate of secondary ACL injury. Purpose: To describe the failure rate and outcomes after a hybrid pediatric ACL reconstruction (ACLR) employing transphyseal hamstring (TPH) autograft combined with an extra-articular technique using an iliotibial band (ITB) autograft. Study Design: Case series; Level of evidence, 4. Methods: Consecutive patients undergoing combined TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 49 publications
4
50
0
2
Order By: Relevance
“…A 2019 case series of 60 adolescents who received a 4-stranded hamstring ACL graft combined with a modified MacIntosh extra-articular tenodesis documented a return to a high activity level with a 5.3% failure rate 38 months after surgery. 35 In still another case series, the Scientific ACL Network International (SANTI) Study Group reported the outcomes of a 4-stranded hamstring graft combined with a 2-armed reconstruction of the ALL. 33 Their patients averaged 24 years old (range, 11-55) and were selected according to anatomic- or activity-related factors that might predispose to an elevated rate of failure.…”
mentioning
confidence: 99%
“…A 2019 case series of 60 adolescents who received a 4-stranded hamstring ACL graft combined with a modified MacIntosh extra-articular tenodesis documented a return to a high activity level with a 5.3% failure rate 38 months after surgery. 35 In still another case series, the Scientific ACL Network International (SANTI) Study Group reported the outcomes of a 4-stranded hamstring graft combined with a 2-armed reconstruction of the ALL. 33 Their patients averaged 24 years old (range, 11-55) and were selected according to anatomic- or activity-related factors that might predispose to an elevated rate of failure.…”
mentioning
confidence: 99%
“…In their study, Gagliardi et al 13 found a median Lysholm score of 99.5 (IQR 89.0 to 100.0) and a median Pedi-IKDC of 94 (IQR 89 to 98) two years after ACLR in children ten to 18 years of age. Wilson et al 14 found a mean Pedi-IKDC of 91.2 (46.7 to 100) at 38.5 months after ACLR in 11- to 16-year-old children. In their literature review, Liechti et al 15 found the Lysholm score ranged between 85.4 and 96.3 at 12 months minimum after meniscal repair, whether or not ACLR was done in patients who averaged 15 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…34 Um estudo recente demonstrou que o uso de tenodese extra-articular lateral associada à reconstrução do LCA transfisária na população pediátrica tem bons resultados (apenas 5% de nova lesão), sem compromisso clinicamente relevante no crescimento do membro inferior intervencionado. 35…”
Section: Discussionunclassified